2015
DOI: 10.1590/1982-0216201517413614
|View full text |Cite
|
Sign up to set email alerts
|

Critérios clínicos utilizados por profissionais para liberação de dieta via oral em pacientes adultos hospitalizados

Abstract: Resumo:OBJETIVO:identificar critérios clínicos utilizados por profissionais para liberação de alimentação via oral em pacientes hospitalizados que apresentam risco para disfagia.MÉTODOS:participaram do estudo 48 profissionais que atuam em dois hospitais gerais de uma cidade do interior do Paraná. Os dados foram coletados por meio da aplicação de um questionário.RESULTADOS:100% dos profissionais consideram o nível de consciência importante para a deglutição, apenas 52,2% vê a importância da presença de deglutiç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
(9 reference statements)
0
5
0
10
Order By: Relevance
“…As to breathing matters, 8% of the patients were under tachypnea and 24% referred dyspnea. It has been observed that disorders in the breathing clinical picture increase the risks of bronchoaspiration due to the incoordination between breathing and swallowing [5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As to breathing matters, 8% of the patients were under tachypnea and 24% referred dyspnea. It has been observed that disorders in the breathing clinical picture increase the risks of bronchoaspiration due to the incoordination between breathing and swallowing [5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Resultsmentioning
confidence: 99%
“…However, due to the great instability presented by many patients in the ICU, care was taken to check whether the level of conscience held itself during the speech-language therapist evaluation, or whether it presented swinging, and this was considered a risk factor, too. Some researches mentioned the minimal score of the Glasgow scale used by some professionals to release the oral diet for the patients 16 . However, this is not our practice, because all the answers presented in the evaluation are considered, so that we can get a more adequate behavior, and the scale is only an aspect to be observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uma delas é o nível de consciência e estado mental, pois é um parâmetro que observa as reações do paciente frente aos estímulos: se sua reação é rápida ou lenta; se se mostra sonolento ou não, sendo um parâmetro essencial para a liberação da dieta via oral para pacientes internados em um hospital. Sabendo que o ato de deglutir pode ocorrer de forma inconsciente, e que devemos estar atentos à manipulação da saliva pelo paciente, é possível prever o comportamento funcional dele com a alimentação via oral baseado na frequência de deglutição espontânea 28,29 .…”
Section: Discussionunclassified